Dampak Bantuan Stimulan Perumahan Swadaya Sebagai Upaya Peningkatan Kesejahteraan Masyarakat Desa Watuagung - Nahdah, Adiibah Afifah; Marseto, Marseto; Oktafia, Renny (Peneliti.net, 2023)
This study aims to determine the impact of the distribution of Self-Help Housing Stimulant Assistance as an effort to improve the welfare of the community in Watuagung Village, Dongko District, Trenggalek Regency. In this study using qualitative research methods through a descriptive approach. This method functions to get an overview of the phenomenon of the problem being observed. Then this study uses primary data types obtained from interviews, observation, and documentation. Then it also uses secondary data types obtained through the Trenggalek Regency Central Bureau of Statistics and Sectoral Data. Where, based on the results of the research, it shows that the distribution of Self-Help Housing Stimulant Assistance has reduced the burden on beneficiaries who are low-income people in order to be able to meet the needs of livable houses so as to improve their welfare. In addition, this assistance has also increased the number of livable houses in the village of Watuagung and encouraged the self-reliance of beneficiaries through empowerment activities during the implementation of the assistance distribution.